PENGARUH TINGKAT KEMATANGAN BIJI BUAH NYAMPLUNG (Calophylum inophylum L.) TERHADAP RENDEMEN MINYAK BIJI BUAH NYAMPLUNG - Noor Mirad Sari; Rosidah Rosidah; Lusyani Lusyani; Ratri Sucityasingrum (Jurnal Riset Industri Hasil Hutan, 2012)
Indonesia which is a net-exporter in of fuel oil has turn become a net importer of oil since 2009. It is ironic because it occurs at the world's oil price is unstable and tends to increase. It is time for Indonesia to develop alternative energy sources and bio-diesel oil from the seeds of  nyamplung (Calophylum inophylum L.). The purpose of this researh was to determine the magnitude of the yield of oil from the seeds of the produced by the level of maturity. The raw and the riped yamplung seeds was used in this research. The results showed that the yield of oil in ripe seed is 24.01% and the raw one is 19.17% . Acid number and iodine number of oil based on the average maturity are 37.51 g / ml and 3094.14 g / ml for the ripe fruit, and 37.18 g / ml and 3421.32 g / ml for the raw fruit.Keywords: nyamplung, maturity, yield, oil, fuel.